Pregnancy outcome with hepatitis E infection - Mayadeo, Niranjan M.; Shah, Sachi N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hepatitis E is usually a self-limited viral infection in men and non-pregnant women, but during pregnancy it is associated with high maternal and perinatal mortality. This needs to be studied for early diagnosis and better management. Methods: The study commenced after the approval of Institutional Ethics Committee. This was a retrospective cum prospective observational study conducted in the Department of Obstetrics and Gynaecology and Department of Medical Intensive Care Unit in present tertiary care hospital between February 2012 and July 2017. An analysis of 120 cases was made over a period of five years. Results: In this study the incidence of pregnant patients with hepatitis E was 3.09 per 1000 deliveries. It was found that majority of the patients which were diagnosed with hepatitis E were young and belonged to the age group of 21-25 years. Most of the affected patients were primigravida with increasing severity of the disease in their third trimester. The maternal morbidity was 51% with a mortality rate of 20%. The percentage of still birth was 25.64% with increased incidence of preterm deliveries and poor perinatal outcome. Conclusions: Early diagnosis and rapid management of the complications such as correction of abnormal coagulation and supportive management is the best treatment available at present. ICU admission and with strict maternal and foetal monitoring can help improve the outcome and thereby reducing the maternal and perinatal mortality.